Palaeostress magnitudes in the Khao Khwang fold-thrust belt, new insights into the tectonic evolution of the Indosinian orogeny in central Thailand - Francesco Arboit (2018)
© 2017 Elsevier B.V. Using the Khao Khwang fold–thrust belt in central Thailand as case study, we handled data from calcite twinning analysis in order to propose the quantification of the effective principal palaeostresses magnitudes since the onset of the early stages of the Indosinian orogeny. We also combined the differential stress estimates from mechanically-induced calcite twins with geochronological data in order to constrain the timing of the palaeoburial depth and subsequent uplift by folding within the Khao Khwang fold–thrust belt. The proposed mechanical scenario is based on the time-constrained kinematic sequence of fracturing, faulting, and folding in the strata of the carbonate formations of the Saraburi Group. Cross-checking the data on the palaeostress orientations, regimes, and differential stress magnitudes with rock mechanics analysis; we provided data on the principal stress magnitudes for each tectonic stage that developed during the Indosinian orogeny. Further, 40 Ar/ 39 Ar and U-Pb geochronological data allowed to place reliable constraints on the amount and rate of vertical uplift of the carbonate formations of the Saraburi Group.